The Consequences of the Schmalcaldic War (1546-1547) for the Development of the Coinage Integration of Europe (Theatrum historiae, 2008)
The author focuses on specific political factors that influenced the creation of II. Imperial Coinage Order of 1551. Every effort was made to reform and unify of coinage situation in the frame of the Holy Roman Empire (the Reich). Emperor Charles V. started it in the times of his predominance between his victory in so called Schmalcaldic war in 1547, and a new military resistance of imperial opposition in 1552. Analysing the process of making of the new imperial currency in 1549-1551, the author comes to the conclusion that the final form of II. Imperial Coinage Order was strongly influenced by the interests of the emperor himself. In the previous decades, Charles V. supported coinage integration of the Reich in the form used by his younger brother Ferdinand I. in his hereditary Austrian lands. However, during the 1540s the emperor gained his own and very important silver mines in the oversea colonies. That's why his own interests in the Reich turned the scale of the long-termed development and why II. Imperial Coinage Order was inconvenient for the Austrian lands. The author judges the final form of II. Imperial Coinage Order as a result of the Charle's policy to integrate the Spanish and imperial coinage systems. It would be much easier for the emperor to apply the oversea silver (they transported so called ship coins, then it was again monetarized for European trade in the Spanish Netherlands or in Naples). Charles V. was, however, shortly defeated by the imperial opposition, after 1555 he lived in seclusion and his project failed. Finally, it was replaced by III. Imperial Coinage Order in 1559, based on the Austrian coinage system.